2007
DOI: 10.1002/app.26810
|View full text |Cite
|
Sign up to set email alerts
|

Multijet electrospinning of conducting nanofibers from microfluidic manifolds

Abstract: We present a method for the electrospinning of conducting polymeric composite nanofibers using a poly(dimethyl siloxane) (PDMS)-based microfluidic device. To scale-up the process and spin multicomponent systems, we designed a unique multi-spinnerette electrospinning device using microchannels cast in PDMS. Nanofibers of poly (vinylpyrrolidone) and its composite with polypyrrole were successfully prepared using one-step and two-step microfluidic electrospinning. The effect of processing variables on the morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 43 publications
2
34
0
2
Order By: Relevance
“…Advantages of this approach include ease of fabrication, flexible control over channel dimensions and geometry, and the potential for multiplexed, multijet electrospinning within a single microfluidic device. 19,25,27 The multilayer microfluidic electrospinning devices used in this study were molded from two-part ͑A:B͒ Sylgard 184 PDMS rubber ͑Dow Corning͒. Positive-relief photoresist molds, used as masters for the microchannel networks, were fabricated using standard lithographic procedures.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Advantages of this approach include ease of fabrication, flexible control over channel dimensions and geometry, and the potential for multiplexed, multijet electrospinning within a single microfluidic device. 19,25,27 The multilayer microfluidic electrospinning devices used in this study were molded from two-part ͑A:B͒ Sylgard 184 PDMS rubber ͑Dow Corning͒. Positive-relief photoresist molds, used as masters for the microchannel networks, were fabricated using standard lithographic procedures.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…While the fiber size distribution is quite high, it can be attributed to both characteristic electrospinning bending instabilities and coulombic repulsion between adjacent jets. 25 The higher-magnification SEM image ͓Fig. 2͑b͔͒ indicates that the single fiber exhibited a bundlelike structure with two small nanofibers bound together.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al have reported that nearly 100 different polymers have been electrospun into ultrafine fibers so far from either polymer solution or melt [55]. Srivastava et al have used microfluidic manifolds to simultaneously spin multiple jets [57] as well as to create core/sheath nanofibers [58]. Figure 1 shows a typical electrospinning setup, which consists of a syringe with a metal needle containing the polymer solution or melt, a metering pump as the feed rate control, a conductive (usually metal) collector, and a high voltage DC power supply.…”
Section: Electrospinning Processmentioning
confidence: 99%
“…So far, several efforts have been made to increase the production rate of nanofibers. For instance, modified single-needle [17,18], multi-needle [19][20][21][22][23][24][25][26][27], needleless systems [28][29][30][31][32][33][34], a plastic filter set-up [35] and forcespinning have been developed to enhance nanofiber production rate. Forcespinning TM or centrifuge spinning uses centrifugal force, rather than electrostatic force, as in the electrospinning process [36].…”
Section: Introductionmentioning
confidence: 99%